Wayside Market, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A vendor selling their vegetable produce by the roadside on vending stands.
Colour: Black and white;Style:Landscape;Other:Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Street vendors; Vending stalls; Vegetables